Severe Human Lower Respiratory Tract Illness Caused by Respiratory Syncytial Virus and Influenza Virus Is Characterized by the Absence of Pulmonary Cytotoxic Lymphocyte Responses - Welliver, Timothy P.; Garofalo, Roberto P.; Hosakote, Yashoda; Hintz, Karen H.; Avendano, Luis; Sanchez, Katherine; Velozo, Luis; Jafri, Hasan; Chavez-Bueno, Susana; Ogra, Pearay L.; McKinney, LuAnn; Reed, Jennifer L.; et al. (The Journal of infectious diseases, 2007)
Background. Respiratory syncytial virus (RSV) and influenza virus are common causes of infantile lower respiratory tract infection (LRTI). It is widely believed that both viral replication and inappropriately enhanced immune responses contribute to disease severity. In infants, RSV LRTI is known to be more severe than influenza virus LRTI. Methods. We compared cytokines and chemokines in secretions of infants surviving various forms of respiratory illness caused by RSV or influenza viruses, to determine which mediators were associated with more-severe illness. We analyzed lung tissue from infants with fatal cases of RSV and influenza virus LRTI to determine the types of inflammatory cells present. Autopsy tissues were studied for the lymphotoxin granzyme and the apoptosis marker caspase 3. Results. Quantities of lymphocyte-derived cytokines were minimal in secretions from infants with RSV infection. Concentrations of most cytokines were greater in influenza virus, rather than RSV, infection. Lung tissues from infants with fatal RSV and influenza virus LRTI demonstrated an extensive presence of viral antigen and a near absence of CD8-positive lymphocytes and natural killer cells, with marked expression of markers of apoptosis. Conclusions. Severe infantile RSV and influenza virus LRTI is characterized by inadequate (rather than excessive) adaptive immune responses, robust viral replication, and apoptotic crisis.